LncRNA FEZF1-AS1 negativno reguliše ETNK1 u cilju promovisanja malignog napredovanja karcinoma bubrega: LncRNA FEZF1-AS1 and renal cell carcinoma - Lou, Jiangyong; Liu, Xiaoming; Fan, Xiaodong; Xu, Xiaoming; Wang, Zhichao; Wang, Liqun (Journal of Medical Biochemistry, 2022)
Background: To explore the role of LncFEZF1-AS1 in renal cell carcinoma (RCC) tissues and cells, and the possible molecular mechanism.Methods: Expressions of LncFEZF1-AS1 in RCC tissues and adjacent ones were detected. The association of LncFEZF1-AS1 level with clinical data of RCC patients was also analyzed. Besides, the differential expressions of LncFEZF1-AS1 in a variety of RCC cell lines were also determined. Then the LncFEZF1-AS1 knockdown model was constructed in RCC cell line to further determine the influences of LncFEZF1-AS1 on the proliferative ability and migration of RCC cells through CCK8 and Transwell experiments. Furthermore, luciferase reporter gene experiment were used to validate the combination of LncFEZF1-AS1 to ETNK1.Results: Results suggested that expression of LncFEZF1-AS1 was noticeably higher in RCC tumor tissues and the RCC cells. Clinical pathological data analysis also suggested that high LncFEZF1-AS1 expression was in correlation with the pathological stage and the incidence of distant metastasis in RCC patients, and the poor overall survival rate. In vitro experiments demonstrated that knocking down of LncFEZF1-AS1 markedly repressed the proliferation and migration of RCC cell lines. Bioinformatics suggested that LncFEZF1-AS1 can interact with the downstream target gene ETNK1, which was confirmed by the luciferase reporter gene experiments. Western Blot results revealed that knocking down of LncFEZF1-AS1 markedly enhanced ETNK1. qRT-PCR analysis indicated that ETNK1 level was under-expressed in RCC tissues and in negative correlation with LncFEZF1-AS1. Further experiments suggested that knockdown of ETNK1 partially reversed the inhibitory effects of LncFEZF1-AS1 silencing on the proliferative and migrative abilities of RCC cells.Conclusions: LncFEZF1-AS1 could facilitation the proliferative and migration of RCC cells by regulating the expression of ETNK1. Therefore, FEZF1-AS1 might function as a cancer-promoting factor and possible new therapeutic target for RCC.